Polynucleobacter paneuropaeus sp. nov., characterized by six strains isolated from freshwater lakes located along a 3000 km north–south cross-section across Europe. Issue 1 (22nd November 2018) - Hoetzinger, Matthias; Schmidt, Johanna; Pitt, Alexandra; Koll, Ulrike; Lang, Elke; Hahn, Martin W.
Abstract : Six Polynucleobacter ( Burkholderiaceae, Betaproteobacteria ) strains isolated from different freshwater lakes located across Europe were taxonomically investigated. Phylogenetic analyses based on 16S rRNA gene sequences assigns all six strains to the cryptic species complex PnecC within the genus Polynucleobacter . Analyses of partial glutamine synthetase ( glnA ) genes suggests that all six strains belong to the species-like taxon designated F15 in previous papers. Comparative genome analyses reveal that the six strains form a genomically coherent group characterized by whole-genome average nucleotide identity (gANI) values of >98 % but separated by gANI values of <88 % from the type strains and representatives of the 16 previously described Polynucleobacter species. In phylogenetic analyses based on nucleotide sequences of 319 orthologous genes, the six strains represent a monophyletic cluster that is clearly separated from all other described species. Genome sizes of the six strains range from 1.61 to 1.83 Mbp, which is smaller than genome sizes of the majority of type strains representing previously described Polynucleobacter species. By contrast, the G+C content of the DNA of the strains is well in the range of 44.8–46.6 mol% previously found for other type strains of species affiliated with the subgroup PnecC. Variation among the six strains representing the new species is evident in a number of traits. These include gene content differences, for instance regarding a gene cluster encoding anoxygenic photosynthesis, as well as phenotypic traits. We propose to name the new species represented by the six strains Polynucleobacter paneuropaeus sp. nov. and designate strain MG-25-Pas1-D2 T (=DSM 103454 T =CIP 111323 T ) as the type strain.